The Influence of Using Video-Based Learning Media on Interest in Learning Marketing Basics in Class X PM Students at SMK Negeri 1 Medan - Hutabarat, Adinda Dwi Melinda Br; Putriku, Aurora Elise (Economic: Journal Economic and Business, 2025)
This study aims to determine the effect of using video-based learning media on students' interest in learning in the subject of Marketing Basics in class X PM SMK Negeri 1 Medan. The background of this study is based on the low interest in learning of students caused by the use of conventional learning media that are less interesting. The method used in this study is a quantitative method with an associative approach. Data collection techniques were carried out through questionnaires distributed to 72 students of class X PM. Data analysis used simple linear regression assisted by the SPSS version 25 program. The results of the study showed that the use of video-based learning media had a positive and significant effect on students' interest in learning. Thus, the use of video media can be an alternative effective learning strategy to increase student participation and enthusiasm for learning in class.